Classical heritage from the epigraphic to the digital : Academia Ragusina 2009 and 2011 - Bratičević, Irena; Radić, Teo; Kurilić, Anamarija; Lučin, Bratislav; Galović, Tomislav; Perić, Olga; Novaković, Darko; Jovanović, Neven, filolog; Tvrtković, Tamara; Rezar, Vladimir; Petrač, Petra; Trachsel, Alexandra; et al. (Zagreb : Ex libris, 2014)
The collection of conference papers Classical heritage from the epigraphic to the digital: Academia Raugisna 2009 & 2011 includes papers from the 2009 and 2011 conferences taking place in Dubrovnik as part of the project supported by Eruopean federation of the national societies of classilac philologists - Euroclassica
Bilješke uz tekst.
Zastupljeni autori: Anamarija Kurilić, Bratislav Lučin, Tomislav Galović, Olga Perić, Darko Novaković, Neven Jovanović, Tamara Tvrtković, Vlado Rezar, Petra Petrač, Alexandra Trachsel, Ninoslav Zubović, Mindaugas Strockis, Josip Degl'Ivellio, Marie Christine Haller Aellig, Voljena Marić, Danijela Hecht-Mijić, Željka Salopek.
Bibliografske bilješke uz tekst.
Sažeci.
Imensko kazalo.